Moroccan EFL Public University Instructors' Perceptions and Self-Reported Practices of Written Feedback - Abderrahim Mamad; Tibor Vígh (National Research University Higher School of Economics, 2022)
Background. Since the 1990s, teachers' written corrective feedback (WCF) has been recognized as vital in addressing linguistic issues or product aspects of writing. However, it is necessary to go beyond error correction and focus on written feedback (WF) that concerns other areas of process writing. Still, teachers' thinking on these issues is often an under-explored area. Purpose. This study aimed to explore EFL instructors' perceptions and their self-reported practices of product- and process-based WF in the writing context of tertiary education. Methods. The exploratory quantitative study collected data from 51 Moroccan EFL writing instructors through a self-developed questionnaire. The questionnaire items regarding perceptions and self-reported practices were valid and acceptable for factor analysis of nine subscales covering the features of product- and process-based WF, and all of them proved to be reliable. This structure allowed several comparisons during data analysis. Results. Concerning product-oriented WF, participants perceived applying WCF and WF modes on the written text as important techniques. As part of process-based WF, most of them highly valued effective WF modes in the writing process. Regarding their self-reported practices of product-based WF, instructors stated that they often employed WF modes on the written text. Within the process-based WF, they reported using judgemental feedback and effective WF modes as their most frequent practices. The comparisons between perceptions and self-reported practices showed mismatches in four subscales, including WCF, content-based WF related to macroaspects of writing, developing evaluative judgement, and effective WF modes in the writing process. Thus, instructors admitted the importance of WF in these areas although they acknowledged applying their practices less frequently. Conclusions. This study verified the psychometric properties of a self-constructed questionnaire, which was justified to be appropriate to explore teachers' perceptions and self-reported practices regarding WF. The results obtained from the different subscales support the effectiveness of WCF and allow the exploration of a new conceptualisation of WF as a process.